Efektivitas Aplikasi Blynk Dalam Monitoring Perpindahan Suplai Daya dan Logging Tegangan Berbasis IoT Pada Sistem ATS-AMF - Defa Maulana Adam Hasibuan; I Gede Dyana Arjana; I Made Suartika; Anak Agung Gede Maharta Pemayun Arjana (Study Program of Magister Electrical Engineering, 2025)
Reliability of electricity supply is crucial for ensuring the continuity of company operations, particularly for server systems. This research designed a prototype IoT-based Automatic Transfer Switch (ATS) and Automatic Main Failure (AMF) system integrated with the Blynk application. The goal was to test whether the Blynk application could monitor power supply switching and automatically store voltage data using the Blynk Cloud Data Logger. This system was developed using a WeMos D1 R32 microcontroller and a PZEM-004T sensor to measure voltage and current from two sources: the state electricity company (PLN) and a generator. Measurement data was displayed in real time in the Blynk application and recorded to the cloud. Testing was conducted over 14 days at one-hour intervals, during which the system was tested under both automatic and manual switching conditions. The results showed that the Blynk application could display power supply switching status with a fast response and accurately log voltage data. This demonstrates the effectiveness of Blynk as a cloud-based monitoring and data logging tool in the IoT-based ATS-AMF power supply system